The regolith-hosted clay REEs leaching effects by mechanical grinding and at low temperature: An analogy on treatment method - Hassan Nasir Mangi; Liqiang Ma; Ru'an Chi; Chenghao Wu; Zhenyue Zhang; Yan DeTian; Lara Sindhu; Khalid Thebo; Umar Ashraf (Journal of Materials Research and Technology)
The leaching effects of regolith-hosted clay particles under mechanical grinding at low temperatures have not been well studied. This study primarily aims to understand how grinding induces intensive pressure, stress, and abrasion on clay particles. Consequently, this may either increase or decrease the surface area and either release or block rare earth elements (REEs ions) embedded in the clay minerals. The adoption of grinding and low-temperature methods applied to different clay horizon samples affects the leaching and adsorption behavior of the particles. This comparative study also provides insight into the intrinsic properties of REEs across different horizons of regolith-hosted clay. High grinding processes can damage the original pore geometry while creating a new pore network in plastic materials like phyllosilicate minerals. XRD-based hidden peaks deconvolution analysis reveals hidden peaks related to the crystallization behavior of halloysite (Al2Si2O5(OH)4). Low temperature suggests that the behavior of ions in micropores influences their fractionation and diffusion processes more effectively than in larger pore spaces. The endogenic gaseous activated energy states refer to the energy of gas molecules, such as water vapor or ammonia, present within the micropores of clay particles during leaching at 50 °C. These gases are energized by heat and grinding, reaching higher energy levels that drive endothermic reactions, facilitating the release of rare earth elements (REEs) through NH4+ ion exchange in both open and closed pore networks. This energy dynamic is crucial for understanding the physical and chemical changes in regolith-hosted clay particles at a constant temperature of 50 °C, as explored in our study. Further research is needed to examine the effects of low-to-medium RPM and low temperatures (50 °C), specifically tailored to the mineralogy and structural changes (e.g., halloysite amorphization) of the samples, in order to optimize leaching efficiency—impacted by these changes—despite the observed variations in the recovery of regolith-based clay REEs in both liberated and unliberated forms across samples.